Numerous cold arousals and rare arousal cascades as a hibernation strategy in European Myotis bats - Blažek, Ján; Zukal, Jan; Bandouchova, Hana; Berková, Hana; Kovacova, Veronika; Martínková, Natália; Pikula, Jiri; Řehák, Zdeněk; Škrabánek, Pavel; Bartonička, Tomáš (Journal of thermal biology, 2019)
Hibernating bats optimise the duration of torpor bouts and arousals in relation to hibernaculum microclimatic conditions and fat reserves. Clustering has significant physiological and ecological benefits, promoting successful hibernation of individuals. Such aggregations may help maintain optimal temperatures, allowing better energy utilisation than in solitarily bats. However, aroused bats in a cluster could conceivably disturb those still hibernating, starting an energy-demanding arousal process. Our study was conducted over two winters in two different hibernacula (cave and mine) in the Czech Republic, where Greater mouse-eared bats (Myotis myotis) have previously been diagnosed with white-nose syndrome. In 118 arousal episodes we recorded 193 individual arousals in which a warming phase was observed, 135 (69.9%) being cold arousals, where bats ceased increasing their body temperatures at ≤ 10 °C. The remaining arousals were standard normothermic arousals, where body (fur) surface temperatures reached > 20 °C. Cold arousals occurred during the mid- and late hibernation periods, suggesting they were a response to disturbance by a neighbour in the same cluster. Arousal cascades, where bats aroused in series, were rare (12.7%) and reached a maximum in mid-January. Our data suggest that Myotis bats prolong their torpor bouts using numerous cold arousals but few arousal cascades. Upon arrival of a bat, the clustered bats show tolerance to disturbing by conspecifics.
Keywords: Clustering behaviour; Behavior, Animal; hibernace; Chiroptera; strnulost; Arousal; Synchronised rewarming; Torpor; tělesná teplota; Animals; Torpor bout; roční období; Seasons; zvířata; Hibernation; arousal; Normothermic and cold arousals; Body Temperature; chování zvířat; Myotis myotis; nízká teplota; Cold Temperature